CONCEPT OF ORGANIZATIONAL DESIGN AND ITS APPLICATION TO THE RESTRUCTURING OF ELECTRIC POWER COMPANIES - Stevanović, Rajko (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2014)
Business organising is a process which performs differentiation and integration of organisation elements. Frequent changes in the environment set an imperative to the management to constantly improve the organisational structure in order to acquire, preserve and upgrade its market position. Organisational design is aimed at the power utility companies debureaucratisation by changing the organisation culture from a technocratic to management culture and towards the redesign of business functions. Organisational structure is being transformed from a functional form to increasingly more team-oriented structure and innovative organisation.